Stress and Temperature Changes of Polymer Woven Belts Subjected to Mechanical Loading - GADAJ, S.P.; PIECZYSKA, Elżbieta A.; NOWACKI, W.K. (Engineering Transactions, 2005)
The experimental results obtained during low-cyclic tensile deformation of woven polyamide belts were presented. The temperature and mechanical characteristics of tension, low-cyclic loading, unloading and stress relaxation processes were found. The temperature changes accompanying the woven belt deformation turned out to differ from those, which were found for the sheet polyamide solid specimens. Such temperature results were caused both by the effects of the material as well as by the effects of the fibrous belt structure. The maximal temperature increments observed during subsequent cycles of loading reached 10 K. The cycling test actually did not affect the stress-strain characteristics of the belts, so it can be concluded that the used belt structure ensures their safe application for various cyclic loadings.